Self-organized nanopatterning of polycarbonate surfaces by argon ion sputtering. (19th June 2018) - Goyal, Meetika; Gupta, Divya; Aggarwal, Sanjeev; Sharma, Annu
Abstract: Polycarbonate surfaces were sputtered using 40 keV Ar + ions at off normal incidence of 30° with ion fluences ranging from 1 × 10 16 Ar + cm −2 to 5 × 10 16 Ar + cm −2 . Surface topography along with structural modification has been studied using atomic force microscope (AFM) and Raman spectroscopy. Substantial smoothing of polymeric surfaces along with evolution of some random dot like nano structures after ion irradiation has been revealed. Average size of dots varied from 34 to 95 nm while density of dots varied from 0.17 to 14.7 × 10 7 dots cm −2 for various ion fluences. Power spectral density spectrum has been obtained from fast Fourier analysis of respective AFM images to get the information about underlying mechanism of sputtering induced nano structuring and smoothing of polymeric surfaces. AFM results have been well correlated with the disordering parameters calculated from the deconvoluted Raman spectra. These nanopatterned substrates are useful in a wide range of important applications, for example, in bioengineering, binary optics, making organic thin-film transistors and light-emitting diodes.